ANALISIS EFEKTIVITAS METODE SEPARATION, ASSESSMENT AND TREATMENT DALAM MANAJEMEN LIMBAH INFEKSIUS DENGAN INTEGRASI ASPEK EKONOMI, LINGKUNGAN DAN KOMPETENSI SDM - Sikki, Nurhaeni; Natalia, Ave; Kevin Usup, Michael; Swandi, Khairfani; Lisalto Usman, Tito (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to evaluate the implementation of the Separation, Assessment, and Treatment method in infectious waste management within healthcare facilities. The primary issues addressed are operational cost inefficiencies resulting from waste mixing, environmental pollution risks, and low staff compliance with Standard Operating Procedures (SOPs). Utilizing a qualitative approach and descriptive analysis, this research integrates three core aspects: economic, environmental, and human resource competence. The results indicate that consistent implementation of the Separation, Assessment, and Treatment method can reduce waste treatment operational costs by 30% by decreasing the volume of infectious waste required to be processed by third parties. Furthermore, this method is proven to minimize hazardous environmental residues and enhance human resource work efficiency through clearer procedural standardization. In conclusion, the integration of human resource competence through continuous training is the key to achieving economic success and environmental sustainability in hospital waste management.